PEMILIHAN BAHASA DALAM RANAH KELUARGA: STUDI KASUS PEMILIHAN BAHASA BUGIS OLEH ETNIS BUGIS DI KABUPATEN DONGGALA SULAWESI TENGAH - NFN Tamrin (Balai Bahasa Sulawesi Tengah, 2013)
The language choice is a maintenance symbol of traditional culture value concept. By using and choosing regional language- in this paper is Bugis - in the family field, have meaning that the traditional culture value concept of Bugis ethnic can be maintenanced. This is because the traditional culture can be well known by its own language. By using the phenomenon of choosing Bugislanguage by Bugis ethnic in the regency of Donggala, The Province of Sulawesi Tengah, the aim in the paper will describe (1) The pattern of Bugis language by Bugis ethnics in family, and (2) the supported factors of the pattern. Method applied in the paper is sociolonguistics approach in givingquesioner technique, interviewing, surveying, and recording. The analysis based on the percentage of choosing the usage of Bugis language pattern in family field. The result shows that the Busgis ethnics in the regency of Donggala as the non-native ethnics, have maintenanced the using of language infamily field, eventhough they have different in age, gender, education, and jobs. Supported factors of choosing Bugis language is loyality, the awareness of language norm, language pride, the age, and jobs.